Pattern of adverse drug reactions to anticancer drugs: A quantitative and qualitative analysis - Shruti Singh; D C Dhasmana; Manisha Bisht; Prashant Kumar Singh (Indian Journal of Medical and Paediatric Oncology)
Introduction: Anticancer drugs contribute significantly to the global burden of adverse drug reactions (ADRs). Any attempt to quantify their magnitude and provide upgraded knowledge would help oncologists in writing safer prescriptions. Aim: This observational follow-up study was conducted on newly diagnosed cancer patients receiving anticancer therapy with an aim to determine the frequency, severity, causality, predictability, and preventability of ADRs. Subjects and Methods: The patients were followed up for 6 months for the appearance of adverse events. Data were analyzed using IBM SPSS Statistics for Windows, Version 22.0. (Armonk, NY) and presented in the form of descriptive statistics. Results: Each patient was prescribed approximately 6.85 ± 1.51 (mean ± standard error) drugs on average. All the patients (100%) receiving anticancer chemotherapy had ADRs. Alopecia, nausea and vomiting, burning tingling, and numbness were the most frequently encountered ADRs. The incidence of alopecia (P < 0.0004), nausea (P < 0.03), and oral ulceration (P < 0.02) was higher in females. Maximum reactions were of Grade 2 (69.53%). Most of the reactions (75.80%) appeared within 10 days of receiving the first cycle. 99.58% reactions were not serious. According to the WHO – The Uppsala Monitoring Centre criteria, 99.47% ADRs fell in possible category. According to the Naranjo's algorithm, 100% ADRs fell in probable category. About 94.80% reactions were found to be predictable. About 56.47% reactions were probably preventable, and 43.53% reactions were not preventable. Conclusion: Multiple ADRs were seen in newly diagnosed cancer patients. Most of them were predictable, of mild-to-moderate severity, nonserious, and preventable. A majority of the ADRs recovered over time.